STRUKTUR MODAL OPTIMAL PADA PERUSAHAAN TELEKOMUNIKASI INDONESIA - Palti Marulitua Sitorus (Jurnal Keuangan dan Perbankan, 2013)
The background of this study was begun with the operational capital needs of telecommunication operators indebt. Bad managing of debt could cause the bankruptcy of the company. The purpose of this research was toknow the optimal capital structure of telecommunication companies in Indonesia. The method used were asimple linear regression and graphs of simulation. The logic was used when a company that used capital withlow cost got high value of company. There were two companies that had an optimal capital structure i.e. PTExcelcomindo Axiata and PT Indosat with optimal capital structure 1, 132 and 1,003.